Ensuring minimum duration of transient processes in switched voltage regulators with digital control - Nepomnyashchiy, Oleg V.; Krasnobaev, Yuri V.; Yablonsky, Aleksey P.; Potekhin, Vyacheslav V.; Sirotinina, Natalia J. (EAI Endorsed Transactions on Energy Web, 2019)
This paper describes a solution suggested to minimize the finite transient duration of a switched voltage regulator (SVR) for step changes in load current. SVR control laws aimed at minimizing the transient time are synthesized, and the microprocessor-based architecture and operating algorithms of the control system are designed. The prototype of the SVR digital control unit is implemented on the field-programmable gate array integrated circuit Cyclone III EP3C120F780 using the NIOS II soft-processor core. Embedded software is developed to calculate the control pulse duration for power switches in accordance with the synthesized control laws taking into account the feedback loop signal. A case study of the prototype shows that it provides the duration of transients caused by a load current step change, equal to 3-4 conversion periods at the frequency of 120 kHz. It confirms the suitability of the developed models, algorithms and control laws for ensuring the minimum transient duration.